Air transport liberalisation in the European Union and its impact on development of the civil aviation sector in Poland - Pisarek, Renata (Comparative Economic Research. Central and Eastern Europe, 2010)
The objective of this paper is to present an overview of the process of air transport liberalisation within the European Community and its influence on development of the aviation market in Poland. The paper describes the stages of air transport liberalisation in the European Community and its implementation to the Polish market. The special focus is given to problems of existing effects of air transport liberalisation and perspectives of its development. The study primarily intends to examine market structure changes of the Polish civil aviation sector and air traffic dynamics over the years of Polish integration with the European Union, presenting the most up-to-date available statistics